A comparison of reward systems for truck drivers based on telematics data and driving behavior assessments - Thomas Bousonville; Christian Ebert; Jasmin Rath (Hochschule für Technik und Wirtschaft des Saarlandes, Fakultät für Wirtschaftswissenschaften, 2015)
This paper investigates the impact of different driving behavior evaluation systems on the distribution of monetary rewards for economic driving. It starts with an introduction into truck telematics systems as the most prominent data source for the assessment metrics. Two specific systems are presented in more detail, focusing on the way driver evaluation is performed in each of them. Data that has been collected from the two systems in a real case is used to analyze if the drivers had a fair chance to get the same bonus independently of the system that was built in their truck.
Keywords: 650; telematics; driving behavior; incentives; award systems